Réponses

  • Utilisateur Brainly
2014-03-26T15:22:22+01:00
A=3(2x -7 ) - 5x=x-21
si x=4 A=-17
si x=0 A=-21
si x=-2 A=-23

B=(x - 4) ( x - 2)=x²-6x+8

si x=4 B=0
si x=0 B=8
si x=-2 B=24

C=(2 - x) au carré
=x²-4x+4
si x=4 A=4
si x=0 A=4
si x=-2 A=16



2014-03-26T15:33:09+01:00
    x=4                x=0                   x= -2


3(2x -7 ) - 5x
Pour X =4
3(2x4-7)-5x4
3(1)-20=-17
X=0
3(-7)-0 =-21
pour X=-2
3(-4-7)+10
3(-11)+10
-33+10=-23

(x - 4) ( x - 2)

X=4 ça donne 0
X=0 ça donne 8
X=-2 ça donne 24
(2 - x) ²

X=4   ça donne 4
X=0 ça donne 4
X=-2 ça donne 8

Pour X=-2 ça donne 16 , une erreur de ma part à la fin